Objective comparison of numerical spin study with aircraft model free-flight spin tests. (February 2023) - Malik, Bilal; Masud, Jehanzeb; Akhtar, Suhail
This paper reports on the results of a research project that investigated the spin and recovery characteristics of a multirole fighter aircraft. In the first phase, numerical/computational methods were used to predict full scale aircraft spin and recovery characteristics. The aerodynamic data used in the numerical study was obtained from rotary balance steady coning and oscillatory coning motion dynamic wind tunnel tests conducted on 1/13 th scale aircraft dynamic model. All the possible steady spin modes were numerically computed, a complete set of dynamic modes of the spinning aircraft were evaluated and six degree of freedom simulations of predicted flat spins were performed to investigate their dynamic stability and recovery characteristics. In the second phase, free-flight spin trials were conducted using 1/5 th scale dynamic model of the understudy aircraft to validate the results of the analytical spin studies. Dynamic characteristics of the analytically predicted flat spins were objectively compared with flat spins found in free-flight spin trials as a validation process. Our results reveal that the numerically predicted full scale aircraft spin and recovery dynamic characteristics correlate well with those estimated from model test flights. The present study is an important step toward objective comparison of numerical spin studies based on dynamic wind tunnel tests data with free-flight spin trials, yielding important guidelines and results for future aircraft spin studies.